Complications in Surgical Management of Recurrent Vulvar Paget’s Disease: Treatment and Follow-up - Šipka, Aleksandar; Đurić, Marina; Tomić, Miroslav; Mandić, Aljoša (Archive of Oncology, 2025)
Introduction: Paget’s disease of the vulva is an intraepithelial adenocarcinoma, primarily arising from vulvar skin glands, with or without an underlying invasive adenocarcinoma. It brings low mortality and a high local recurrence rate and mainly affects postmenopausal women. Case outline: This is a case report of a 57-year-old postmenopausal woman, who had histopathological (HP) verified Extramammary Vulvar Paget’s disease (EVPD) in 2014, and underwent a radical vulvectomy with a right-sided inguinofemoral lymphadenectomy and V-Y flap at the Oncology Institute of Vojvodina. Nine years later, in 2023, the patient was presented with a biopsy HP proven EVPD recurrence. The recurrence was surgically treated with vulvectomy and bilateral fasciocutaneous V-Y flaps reconstruction. The operative HP specimen proved the EVPD recurrence with atypical cells on one edge of the specimen. Due to the infection-complicated healing and wound dehiscence, the first reoperation was performed, which included wound debridement and left-sided rotational flap. We carried out the wound care and toileting in the postoperative course, with antibiotic treatment. Due to infection-complicated healing, tissue necrosis and consequent dehiscence, the second reoperation was performed, which included wound debridement with granulation tissue excochleation and Tiersch-type skin graft. Conclusion: The patient was discharged 21 days after the second reoperation in good condition. A regular oncological postsurgical follow-up on the 3th and 6th month revealed no recurrence or deterioration of the general condition or local findings. The patient subjectively feels well and has no complaints or unwanted effects of the applied treatment.